2021
DOI: 10.1111/inm.12926
|View full text |Cite
|
Sign up to set email alerts
|

'You get this conflict between you as a person and you in your role…that changes you': A thematic analysis of how inpatient psychiatric healthcare staff in the UK experience restraint, seclusion, and other restrictive practices

Abstract: A high proportion of psychiatric inpatients experience Restrictive Practice (RP) during admission. Numerous reports have highlighted adverse effects on patients and staff. However, qualitative research focussed on experience, impact, and coping mechanisms of healthcare staff in the UK is limited. Therefore, this study explored psychiatric healthcare staff experience of RP on inpatient wards in the UK. Eight semi‐structured, audio‐recorded interviews, of ~60 min, were conducted via telephone/Skype and transcrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…This was more of an issue for senior staff with greater experience in the system who felt that they should be able to decide when and how patients are restrained. The finding is in keeping with recent UK research which reports that while junior staff initially challenge the status quo, over time they accept restraint as usual practice (Mooney & Kanyerediz 2021).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This was more of an issue for senior staff with greater experience in the system who felt that they should be able to decide when and how patients are restrained. The finding is in keeping with recent UK research which reports that while junior staff initially challenge the status quo, over time they accept restraint as usual practice (Mooney & Kanyerediz 2021).…”
Section: Discussionsupporting
confidence: 86%
“…The overarching theme to emerge from this and previous studies in Australia and elsewhere is the perceived need among nursing staff for the ongoing use of physical restraint in inpatient facilities (Mooney & Kanyeredzi 2021;Muir-Cohcrane et al 2018). However, nursing staff expressed a sense of disempowerment and anger that 'external controls' were being placed on their practice through policy change.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…These evaluations are included in the bigger picture of the assessments of patients’ readiness to be released from mechanical restraints (Nielsen et al, 2018 ). A recent qualitative study reported the impacts on the professional relationships when patients stopped engaging positively with healthcare professionals after restrictive practice, exacerbating the professionals` feelings of guilt (Mooney & Kanyeredzi, 2021 ). Today, the field of mental health nursing suggests different levels of assessments related to basic physiological needs, symptoms experienced (Barker, 2004 ), and elements such as risk, physical and mental status, symptomatology and effects of medication (Gamble & Brennan, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, strategies to reduce the use or duration of seclusion may be valuable. Researchers have begun investigating the adverse effect of restraint and seclusions on the psychiatric staff involved (e.g., Mooney & Kanyeredzi 2021), and the present study may further motivate such efforts.…”
Section: Relevance For Clinical Practicementioning
confidence: 89%